A Superoxide-Hypersusceptible Salmonella enterica Serovar Typhimurium Mutant Is Attenuated but Regains Virulence in p47(phox−/−) Mice - van Diepen, Angela (American Society for Microbiology, 2002)

(untitled)
Salmonella enterica serovar Typhimurium is a gram-negative, facultative intracellular pathogen that predominantly invades mononuclear phagocytes and is able to establish persistent infections. One of the innate defense mechanisms of phagocytic cells is the production of reactive oxygen species, including superoxide. S. enterica serovar Typhimurium has evolved mechanisms to resist such radicals, and these mechanisms could be decisive in its ability to survive and replicate within macrophages. Recently, we described a superoxide-hypersusceptible S. enterica serovar Typhimurium mutant strain, DLG294, that carries a transposon in sspJ, resulting in the lack of expression of SspJ, which is necessary for resistance against superoxide and replication within macrophages. Here we show that DLG294, which is a 14028s derivative, hardly induced any granulomatous lesions in the livers upon subcutaneous infection of C3H/HeN (Ity(r)) mice with 3 × 10(4) bacteria and that its bacterial counts were reduced by 3 log units compared to those of wild-type S. enterica serovar Typhimurium 14028s on day 5 after infection. In contrast, DLG294 replicated like wild-type S. enterica serovar Typhimurium 14028s and induced a phenotypically similar liver pathology in p47(phox−/−) mice, which are deficient in the p47(phox) subunit of the NADPH oxidase complex and which do not produce superoxide. Consistent with these results, DLG294 reached bacterial counts identical to those of wild-type S. enterica serovar Typhimurium 14028s in bone marrow-derived macrophages from p47(phox−/−) mice and in X-CGD PLB-985 cells at 24 h after challenge. These results indicate that SspJ plays a role in the bacterium's resistance to oxidative stress and in the survival and replication of S. enterica serovar Typhimurium both in vitro and in vivo.